1990
DOI: 10.1002/mrm.1910150302
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo NMR spectroscopy of lithium‐7 in humans

Abstract: The pharmacokinetics of lithium uptake was measured by 7Li NMR spectroscopy at 24.83 MHz in vivo in the brain and muscle of a normal subject and a patient suffering from bipolar affective disorder, using a modified General Electric Signa clinical magnetic resonance imaging system. Comparison was made to standard phantoms to estimate Li concentrations. The levels of Li in brain and muscle were similar, were typically less than the level in serum, and generally tracked the level in serum. The Li level at steady … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(16 citation statements)
references
References 23 publications
(9 reference statements)
0
15
0
1
Order By: Relevance
“…Sodium-23 NMR visibility in RBCs has been the subject of some controversy (12,35,36) At therapeutic dosages of Li in humans, serum and tissue Li levels are in the 1 m M range (8). It is reasonable to expect the motional and spin relaxation properties of ions in biological systems with a fixed number of binding sites to be concentration dependent.…”
Section: ( 2 1 -I )mentioning
confidence: 99%
“…Sodium-23 NMR visibility in RBCs has been the subject of some controversy (12,35,36) At therapeutic dosages of Li in humans, serum and tissue Li levels are in the 1 m M range (8). It is reasonable to expect the motional and spin relaxation properties of ions in biological systems with a fixed number of binding sites to be concentration dependent.…”
Section: ( 2 1 -I )mentioning
confidence: 99%
“…(24. 25). It is noted that the 0-ATP resonance with the same T2 of 20 ms as PDE ( 2 4 ) has a large amplitude.…”
Section: Simulation and Experimental Resultsmentioning
confidence: 94%
“…The feasibility of in vivo lithium MRS first was described by Renshaw et al [50] and then in humans by Komoroski et al [51]. Gyulai et al [52] found a positive correlation between occipital brain, serum, and muscle lithium levels of patients with bipolar disorder.…”
Section: Lithium Magnetic Resonance Spectroscopymentioning
confidence: 97%